The Artistic Functioning of the Concept of "Mountain" in the Works of Russian and Tatar Writers of the Second Half of the Twentieth Century (On the Example of the Works by V. Astafyev and A. Eniki) - Gilazova, Svetlana F.; Motigullina, Alfiya R.; Golikova, Guzel A.; Zamalieva, Luiza F.; Naumova, Natalya (Journal of History Culture and Art Research, 2017)
Studying the key concepts of languages is important for linguistics and literature. In this research, the authors refer to the concept "mountain" in its various modifications, presented in the works of Tatar and Russian writers of the second half of the twentieth century. Some mythological aspects of the implementation of the concept "mountain" are examined in works of Russian and Tatar writers (V. Astafyev and A. Eniki), which are based on mythological and folklore traditions. The authors mark out semantic oppositions "mountain – sky", "mountain - the knowledge of meaning of life"," mountain- basis of life", "life-death", which determine the space-time model of works and the national identity of the authors. At the same time the two authors are similar in the ideological basis of their texts, using popular and mythological invariant of the concept of mountain in its positive connotation, despite the difference of story organization of works. First of all, the mountain marks the basis of life. They are determined by high moral position and integrated with the motive of miracle (through the miracle of love). Although the miracle of love in the works of Astafyev is fragile and cannot stand before the impact of human civilization and the miracle of the appearance of the great-grandson of Eniki (also through the miracle of love) is more earthly and strong.